Dermatological alterations in women working on dairy farm: a case study - Vaz, Marta Regina Cezar; Bonow, Clarice Alves; Borges, Anelise Miritz; Almeida, Marlise Capa Verde de; Rocha, Laurelize Pereira; Severo, Luana de Oliveira (Ciência rural, 2013)
The present study aims to identify dermatological alterations due to the work carried out by women on dairy farms and presents an intervention process on dermatology health with women working in these locations. It is a quasi-experimental study, in an intervention form, in which each subject is independent. It was performed with 20 women working on a dairy farm in Rio Grande, Rio Grande do Sul, Brazil, between July and October 2011. Most (60%) women identified dermatological changes due to the work. During the intervention, dermatological care action was focused on. The knowledge of these results offers valuable information for those who teach and advice people about dermatological care in rural working places, where such rates of occurrence are high. O presente estudo teve como objetivos identificar alterações dermatológicas decorrentes do trabalho de mulheres trabalhadoras de ordenha mecânica animal e apresentar um processo de intervenção sobre a saúde dermatológica com mulheres trabalhadoras de ordenha mecânica animal. Um estudo quase-experimental de intervenção, em que cada sujeito é controle dele mesmo, foi conduzido com 20 mulheres trabalhadoras de ordenha mecânica animal em Rio Grande, Rio Grande do Sul, Brasil, entre julho e outubro de 2011. A maioria (60%) das mulheres identificaram alterações dermatológicas decorrentes do trabalho. Durante intervenção, foram enfocadas ações de cuidados dermatológicos. O conhecimento desses resultados são informações valiosas para aqueles que ensinam e aconselham sobre cuidados dermatológicos nos locais de trabalho rural, local em que as taxas de lesões são altas.